The Dead Sea Scrolls in the Context of Hellenistic Judea : Proceedings of the Tenth Meeting of the International Organization for Qumran Studies (Aberdeen, 5-8 August, 2019) - Hartog, Pieter B.; Perrin, Andrew (Studies on the Texts of the Desert of Judah, 2022)
This volume situates the Qumran Dead Sea Scrolls within Hellenistic Judea. By so doing, this volume shows how the Dead Sea Scrolls participate in broad, cross-cultural intellectual discourses that surpass the Jewish group that produced and collected these scrolls.